High Prevalence of Medication Discrepancies Between Home Health Referrals and Centers for Medicare and Medicaid Services Home Health Certification and Plan of Care and Their Potential to Affect Safety of Vulnerable Elderly Adults. Issue 11 (27th September 2016) - Brody, Abraham A.; Gibson, Bryan; Tresner‐Kirsch, David; Kramer, Heidi; Thraen, Iona; Coarr, Matthew E.; Rupper, Randall
Abstract : Objectives: To describe the prevalence of discrepancies between medication lists that referring providers and home healthcare (HH) nurses create. Design: The active medication list from the hospital at time of HH initiation was compared with the HH agency's plan of care medication list. An electronic algorithm was developed to compare the two lists for discrepancies. Setting: Single large hospital and HH agency in the western United States. Participants: Individuals referred for HH from the hospital in 2012 (N = 770, 96.3% male, median age 71). Measurements: Prevalence was calculated for discrepancies, including medications missing from one list or the other and differences in dose, frequency, or route for medications contained on both lists. Results: Participants had multiple medical problems (median 16 active problems) and were taking a median of 15 medications (range 1–93). Every participant had at least one discrepancy; 90.1% of HH lists were missing at least one medication that the referring provider had prescribed, 92.1% of HH lists contained medications not on the referring provider's list, 89.8% contained medication naming errors. 71.0% contained dosing discrepancies, and 76.3% contained frequency discrepancies. Conclusion: Discrepancies between HH and referring provider lists are common. Future work is needed to address possible safety and care coordination implications of discrepancies in this highly complex population.